2014
DOI: 10.1016/j.ecolind.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Species indicators of ecosystem recovery after reducing large herbivore density: Comparing taxa and testing species combinations

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…The concomitant use of several species makes sense, however, since each indicator species is not always present and because the averaging of measurements on several species is likely to increase the reliability of the indicator. Recently, experimental work based on controlled browsing enclosures has identified species combinations that could be used as indicators of browsing pressure and has suggested using them to monitor ecosystem recovery after reducing herbivore densities (Bachand et al 2014). Here, we raise the issue of identifying assemblages of species that vary along a gradient of browsing pressure, not only spatially as in the previous studies to date but also temporally.…”
Section: Response Of Vegetation Communities To Decreasing Deer Browsimentioning
confidence: 89%
“…The concomitant use of several species makes sense, however, since each indicator species is not always present and because the averaging of measurements on several species is likely to increase the reliability of the indicator. Recently, experimental work based on controlled browsing enclosures has identified species combinations that could be used as indicators of browsing pressure and has suggested using them to monitor ecosystem recovery after reducing herbivore densities (Bachand et al 2014). Here, we raise the issue of identifying assemblages of species that vary along a gradient of browsing pressure, not only spatially as in the previous studies to date but also temporally.…”
Section: Response Of Vegetation Communities To Decreasing Deer Browsimentioning
confidence: 89%
“…Vegetation-based indices (i.e., phytoindicators) of browsing are typically preferred as they allow a rapid and costeffective assessment of browse impacts on forest communities (Iijima and Nagaike, 2015). Vegetation indicators include browse surveys (Oak browsing index; Chevrier et al, 2012; Sugar maple browse index; Frelich and Lorimer, 1985), measurements of morphological characteristics of browse-sensitive species (e.g., height or impact to reproductive structures; reviewed by Kirschbaum and Anacker, 2005), demographic characteristics of plant populations (Knight, 2003;McGraw and Furedi, 2005), and even integrated indices that consider responses at the plant community-level (Filazzola et al, 2014;Frerker et al, 2013) or across taxonomic groups (e.g., plants and insects; Bachand et al, 2014). Ultimately, monitoring browse indicators provides managers critical data to sustainably manage their resources.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Red Crossbills are more efficient in foraging on closed cones than White-winged Crossbills and the predicted foraging efficiency of percna is higher than other Red Crossbills mainly based on the size of its bill (Benkman 1987 We expected Red Crossbills to be associated with mature forest stands, but most of our Red Crossbill observations occurred in relatively young forests stands dominated by white spruce, although we acknowledge that we surveyed only the central region of the island. Indeed, a recent study reported that Red Crossbills are indicators of mature conifer forests with high deer density on Anticosti Island (Bachand et al 2014). Although our results are not congruent with Bachand et al (2014), spruce budworm infestations during our survey may have influenced foraging behaviors of Red Crossbills.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study reported that Red Crossbills are indicators of mature conifer forests with high deer density on Anticosti Island (Bachand et al 2014). Although our results are not congruent with Bachand et al (2014), spruce budworm infestations during our survey may have influenced foraging behaviors of Red Crossbills. Accordingly, 20% of Red Crossbill observations occurred in forest stands mapped as infested by spruce budworms, and up to 75% of observations were within 1 km of mapped infested stands.…”
Section: Discussionmentioning
confidence: 99%